Pro Puppet - Turnbull, James. (Apress : Imprint: Apress, 2011)
Pro Puppet is an in-depth guide to installing, using, and developing the popular configuration management tool Puppet. The book is a comprehensive follow-up to the previous title Pulling Strings with Puppet. Puppet provides a way to automate everything from user management to server configuration. You'll learn how to create Puppet recipes, extend Puppet, and use Facter to gather configuration data from your servers. Puppet is a must-have tool for system administrators, and Pro Puppet will teach you how to maximize its capabilities and customize it for your environment. Install and configure Puppet to immediately start automating tasks and create reporting solutions Learn insider tricks and techniques to better manage your infrastructure Become a Puppet expert!